Influence of soft elements on KM implementation in Malaysian higher learning institutions - Yip, Mum Wai (The Leadership Alliance Inc., 2010)

(untitled)
Knowledge Management (KM) is an approach in identifying, acquiring, applying, sharing, creating, developing, preserving and measuring the knowledge of the organization. However, recent global analyses of such KM initiatives highlight the fact that not all of them are necessarily successful. The reason is due to the efforts on technology. Practitioners are now realizing the importance of the soft aspects of KM initiatives. Moreover, there is an organizational lack of data and information on the soft elements of critical success factors of KM. The main purpose of this study is to examine the relationship between the soft elements of critical success factors and KM perceived benefits. This study was accomplished through questionnaires that surveyed 99 higher learning institutions that are located in the Malaysia. Findings revealed that organizational culture and top management leadership have a positive relationship with the perceived benefits of KM.